International Procurement and Supply Network Management in the Post COVID 19 Era in Nigeria: A Literature Review - Akintokunbo, Oluwarotimi; Arimie, Biebele (Journal of Strategic Management, 2021)
Introduction: The global economy has been greatly affected by the outbreak of the COVID-19 pandemic and its impact on the oil and gas industry is also being felt immensely as the industry relies heavily on the importation of the goods and services that they require to run their operations effectively and efficiently and the only way to get to the final destination of these company is through a well-managed supply network. Purpose: The purpose of this study was to examine international procurement and supply network management in the post COVID 19 Era in Nigeria. Being a literature review, the paper adopted a desk research methodology. Findings: The findings of the review of literature reveal that international procurement significantly influence and predicts supply network management performance. It also shows that COVID-19 has negatively affected both international procurement and supply network management, and that the phrase supply network management, instead of supply chain management, is most appropriate to describe the activities and relationships between and amongst individuals, enterprises, facilities and information, materials and services systems that connects supplier's suppliers to customer's customers capturing the multiple and complex relationships that exists amongst them.